De-Colonizing Australia's Commemorative Landscape: "Truth-Telling, " Contestation and the Dialogical Turn. Issue 4 (2nd October 2022) - Scates, Bruce; Yu, Peter
ABSTRACT: This article will explore the origins and afterlife of the Explorers' Memorial in Fremantle, Western Australia. Raised to commemorate the "murder" of white pioneers in the 1860s, the monument issued an explicit denial of Indigenous sovereignty and exonerated white violence on the frontier. In an instance of dialogical memorialization, an additional plaque was placed on the monument. It outlines the history of provocation that led to the explorers' deaths, acknowledges the right of Aboriginal people to defend their lands and commemorates those who died during the invasion of their country. The article will draw on community memory as well as white archival accounts. It will reveal the spaces counter-memorialization might offer for alternative readings of the past and explore the monument's transition from a symbol of racism and division to a platform for what is generally known in Australia as truth-telling and reconciliation.